224 aEEG and NIRS During Transition after Birth. (October 2012) - Pichler, G; Avian, A; Binder, C; Zotter, H; Schmölzer, GM; Morris, N; Müller, W; Urlesberger, B
Abstract : Background and aims: Easily applicable non-invasive devices to monitor cerebral activity and oxygenation continuously during neonatal transition and resuscitation are lacking. We aimed to identify a method of directly monitoring cerebral activity and oxygenation during transition and resuscitation after birth. Methods: Neonates >34 weeks gestation born via caesarean section were included. Cerebral activity was continuously measured with amplitude integrated EEG (aEEG) and cerebral oxygenation (rSO2) with near-infrared-spectroscopy during the first ten minutes after birth. For quantitative analysis of aEEG the mean minimum amplitude (Vmin) and maximum amplitude (Vmax) was determined at every minute. Neonates with normal transition were compared to neonates with need of resuscitation. Results: Out of 224 eligible neonates 63 were included and 46 had reliable measurements: 31 with normal transition and 15 in need of resuscitation. Neonates with normal transition showed higher values for Vmin in the third minute and higher values for Vmax in the third and fourth minute compared to minute 10. Neonates requiring respiratory support had lower values for Vmin in the ninth minute compared to minute 10. In neonates with normal transition rSO2 values during the first six minutes were lower when compared to minute 10. rSO2 values in neonates requiring respiratory support remained lower over the first eight minutes when compared to minute 10. Conclusions: This is the first study demonstrating the feasibility of aEEG and rSO2 monitoring during neonatal transition. The cerebral activity pattern in compromised infants requiring resuscitation was different when compared to infants with normal transition.